Competence gap of board members cooperatives in Malaysia / Rosmalina Che Yakzam ... [et al.] - Che Yakzam, Rosmalina; Mahmood, Norfaezah; Nor Hamid, Nor Irzaq; Ismail, Azianti; Hashim, Adila; Abu Bakar, Siti Nuraini; Hamsan, Nur Yazira (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The National Entrepreneurship Policy (NEP2030) aims to contribute RM100 billion in cooperative revenue by the year 2030. This can be seen because cooperatives play an important role in contributing to the economic development of Malaysia. However, the effectiveness of cooperatives depends on the competence of Cooperative Board Members (CBM) in carrying out their duties and responsibilities as catalysts in the cooperative movement. Nevertheless, research on the current competence gap in CBM is still lacking. Competence gap among CBM is often an obstacle in achieving excellent performance. The approach of this study can help CBM to build personal competence and can be used as an effort to improve organizational performance through competency empowerment. Accordingly, this study aims to identify current CBM competency gaps based on 44 competency items and five task areas. By using quantitative research methods, questionnaires were distributed to 420 people from 14 states in Malaysia. The research data collected was analysed using the Rasch Measurement Model with Winstep 5.2.20. The results of the analysis show that the most difficult item for CBM to implement is conducting business activities through digital channels. The study also found that financial management is the most difficult task for CBM. The results of this study provide important implications for agencies related to cooperatives, such as the Malaysian Co-operative Societies Commission (MCSC), and the Cooperative Institute of Malaysia (CIM), so that they can provide appropriate training and guidance and focus on the cooperative movement.